(w-9)*(w+4)=

Simple and best practice solution for (w-9)*(w+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-9)*(w+4)= equation:


Simplifying
(w + -9)(w + 4) = 0

Reorder the terms:
(-9 + w)(w + 4) = 0

Reorder the terms:
(-9 + w)(4 + w) = 0

Multiply (-9 + w) * (4 + w)
(-9(4 + w) + w(4 + w)) = 0
((4 * -9 + w * -9) + w(4 + w)) = 0
((-36 + -9w) + w(4 + w)) = 0
(-36 + -9w + (4 * w + w * w)) = 0
(-36 + -9w + (4w + w2)) = 0

Combine like terms: -9w + 4w = -5w
(-36 + -5w + w2) = 0

Solving
-36 + -5w + w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-4 + -1w)(9 + -1w) = 0

Subproblem 1

Set the factor '(-4 + -1w)' equal to zero and attempt to solve: Simplifying -4 + -1w = 0 Solving -4 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1w = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1w = 0 + 4 -1w = 0 + 4 Combine like terms: 0 + 4 = 4 -1w = 4 Divide each side by '-1'. w = -4 Simplifying w = -4

Subproblem 2

Set the factor '(9 + -1w)' equal to zero and attempt to solve: Simplifying 9 + -1w = 0 Solving 9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1w = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1w = 0 + -9 -1w = 0 + -9 Combine like terms: 0 + -9 = -9 -1w = -9 Divide each side by '-1'. w = 9 Simplifying w = 9

Solution

w = {-4, 9}

See similar equations:

| (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 | | 32x^2-332x+8=0 | | 6x+8=4(x+9) | | 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 | | 5(4d+8)=80 | | n(17+x)=34x-r | | 14a+20= | | y-5=28 | | 16x-3=86 | | 4(7t+1)-10=t-(t+5) | | 6(y+5)=-36 | | 3x-16=86 | | (2x^7-8y^8)(4x^6+6y^2)= |

Equations solver categories